Understanding anorexia nervosa - Stanley, Debbie (New York : Rosen Pub. Group, 1999)
Discusses the causes and consequences of anorexia nervosa, as well as ways to treat and prevent this condition.
Includes bibliographical references (p. 98-100) and index.
Keywords: Anorexia nervosa -- Juvenile literature; Eating disorders -- Juvenile literature; Anorexia nervosa; Eating disorders